Employability and career experiences of international graduates of MSc Public Health: a mixed methods study. (July 2018) - Buunaaisie, C.; Manyara, A.M.; Annett, H.; Bird, E.L.; Bray, I.; Ige, J.; Jones, M.; Orme, J.; Pilkington, P.; Evans, D.
Abstract: Objectives: This article aims to describe the public health career experiences of international graduates of a Master of Science in Public Health (MSc PH) programme and to contribute to developing the evidence base on international public health workforce capacity development. Study design: A sequential mixed methods study was conducted between January 2017 and April 2017. Methods: Ninety-seven international graduates of one UK university's MSc PH programme were invited to take part in an online survey followed by semistructured interviews, for respondents who consented to be interviewed. We computed the descriptive statistics of the quantitative data obtained, and qualitative data were thematically analysed. Results: The response rate was 48.5%. Most respondents (63%) were employed by various agencies within 1 year after graduation. Others (15%) were at different stages of doctor of philosophy studies. Respondents reported enhanced roles after graduation in areas such as public health policy analysis (74%); planning, implementation and evaluation of public health interventions (74%); leadership roles (72%); and research (70%). The common perceived skills that were relevant to the respondents' present jobs were critical analysis (87%), multidisciplinary thinking (86%), demonstrating public health leadership skills (84%) and research (77%). Almost all respondents (90%) were confident in conducting research. Respondents recommended the provision of longer public health placement opportunities, elective courses on project management and advanced statistics, and 'internationalisation' of the programme's curriculum. Conclusions: The study has revealed the relevance of higher education in public health in developing the career prospects and skills of graduates. International graduates of this MSc PH programme were satisfied with the relevance and impact of the skills they acquired during their studies. The outcomes of this study can be used for curriculum reformation. Employers' perspectives of the capabilities of these graduates, however, need further consideration. Highlights: International graduates have confidence in the skills they gained from a UK masters in a public health programme. Critical appraisal, project management and research skills were highly valued. Most graduates reported career advancement after successful completion of the masters programme. Further placement opportunities and advanced statistics were recommended to enhance career development.